Intercultural interferences in technical translation: A glance at Italian and German technical manuals - Hempel, Karl Gerhard (The Journal of Specialised Translation, 2009)
This paper presents a corpus-based study, the aim of which is to define translation-relevant, culture-bound features of Italian technical manuals and their impact on translation decisions. Italian texts are found to be distinguished by a ‘high’, somewhat ‘scientific’ register which in turn is characterised by markedly explicit formulations. Distance between writer and reader is underlined by certain linguistic markers and bureaucratic expressions. The specific stylistic and pragmatic features of the source texts may cause difficulties to translators, if they fail to take into account the different text-type-bound conventions in source and target culture. The quality of the German translations in our corpus appears at times to be compromised by cases of intercultural interference which could be avoided, if translators were trained better. The paper includes a series of examples, comparing adequate and inadequate translation solutions.